The Ribulose Monophosphate Pathway Substitutes for the Missing Pentose Phosphate Pathway in the Archaeon Thermococcus kodakaraensis - Orita, Izumi (American Society for Microbiology, 2006)
The ribulose monophosphate (RuMP) pathway, involving 3-hexulose-6-phosphate synthase (HPS) and 6-phospho-3-hexuloisomerase (PHI), is now recognized as a widespread prokaryotic pathway for formaldehyde fixation and detoxification. Interestingly, HPS and PHI homologs are also found in a variety of archaeal strains, and recent biochemical and genome analyses have raised the possibility that the reverse reaction of formaldehyde fixation, i.e., ribulose 5-phosphate (Ru5P) synthesis from fructose 6-phosphate, may function in the biosynthesis of Ru5P in some archaeal strains whose pentose phosphate pathways are imperfect. In this study, we have taken a genetic approach to address this possibility by using the hyperthermophilic archaeon Thermococcus kodakaraensis KOD1. This strain possesses a single open reading frame (TK0475) encoding an HPS- and PHI-fused protein. The recombinant HPS-PHI-fused enzyme exhibited the expected HPS and PHI activities in both directions (formaldehyde fixing and Ru5P synthesizing). The TK0475 deletion mutant Δhps-phi-7A did not exhibit any growth in minimal medium, while growth of the mutant strain could be recovered by the addition of nucleosides to the medium. This auxotrophic phenotype together with the catalytic properties of the HPS-PHI-fused enzyme reveal that HPS and PHI are essential for the biosynthesis of Ru5P, the precursor of nucleotides, showing that the RuMP pathway is the only relevant pathway for Ru5P biosynthesis substituting for the classical pentose phosphate pathway missing in this archaeon.